Novel removal of Anthracene from oil-contaminated water by synthesized modified magnetic nano-particles - Torabian, Azadeh; Panahi, H. Ahmad; Bidhendi, G.R. Nabi; Mehrdadi, N. (JOURNAL OF ADVANCES IN CHEMISTRY, 2014)
Novel magnetic nanoparticles (MNPs) modified with (3-mercaptopropyl)-trimethoxysilane (MPTMS), grafted with allyl glycidyl ether and coupled with beta naphthol, were prepared for removal of anthracene in aqueous solutions. The grafted MNPs were characterized by transmission electron microscopy (TEM), infrared spectroscopy (FT-IR) and thermogravimetric analysis (TGA). The modified MNPs contributed to enhancement of the adsorption capacity and were prepared by co-precipitation. The modified MNPs were characterized by TEM, FT-IR and TGA and the adsorption and kinetic behavior of anthracene on the modified MNPs was examined. It was shown that the nano-adsorbent optimized adsorption capacity is at pH 7. Three kinetics models: pseudo-first-order, pseudo-second-order, and intraparticle diffusion were used to investigate the adsorption mechanism of the anthracene onto the modified MNPs. The best fit was obtained for the pseudo-second-order model. The synthesized nano adsorbent can be considered as a new method for anthracene adsorption in contaminated water with the benefit of fast removal by applying a magnetic field.